The positive correlation between psoriasis vulgaris severity degree with HbA1C level - Made Swastika Adiguna; Made Wardhana; Fresa Nathania Rahardjo (Explorer Front, 2018)
Introduction: Psoriasis is a skin abnormality based on chronic inflammation immune-mediated. Insulin resistance and psoriasis seem to have a connection, but it has not been explained clearly. HbA1c describe the glucose concentration and demonstrate the insulin resistance condition indirectly. Objective: This study aims to understand the correlation between psoriasis vulgaris severity degree with HbA1c. Material and methods: This study was using a cross sectional method. Psoriasis vulgaris diagnosed clinically and assessed with the PASI score. The HbA1c level examination done by drawing venous blood then analyzed with chromatography method. Samples were selected by using inclusion and exclusion criteria and a consecutive sampling method. Results: Total 51 subjects (33 subjects with psoriasis vulgaris and 18 subjects without psoriasis vulgaris) were included in this study. Mostly (57.6%) of the subject was mild, 24.2% moderate, and 18.2% severe psoriasis. HbA1c level of psoriasis vulgaris subjects is significantly higher than non-psoriasis vulgaris subjects (p=0.019, PR=6.545). Correlation between severity degree and HbA1c level found in positive course significantly with moderate strength of correlation (r = 0.580, p<0.001). Conclusion: HbA1c level on psoriasis vulgaris subjects are higher than non-psoriasis vulgaris. Psoriasis vulgaris severity degree positively correlated with HbA1c.